2017
DOI: 10.1007/s00414-016-1529-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of RAGE expression and its application to diabetic wound age estimation

Abstract: With the prevalence of diabetes, it is becoming important to analyze the diabetic wound age in forensic practice. The present study investigated the time-dependent expression of receptor for advanced glycation end products (RAGE) during diabetic wound healing in mice and its applicability to wound age determination by immunohistochemistry, double immunofluorescence, and Western blotting. After an incision was created in genetically diabetic db/db mice and control mice, mice were killed at posttraumatic interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…[6,11]. Also in various studies reported that there were different repair processes between diabetic and non-diabetic wounds [9]. These findings supported that in our study why wound healing effects of Luteolin in non-diabetic were higher than diabetic.…”
Section: Histopathological Studysupporting
confidence: 91%
See 2 more Smart Citations
“…[6,11]. Also in various studies reported that there were different repair processes between diabetic and non-diabetic wounds [9]. These findings supported that in our study why wound healing effects of Luteolin in non-diabetic were higher than diabetic.…”
Section: Histopathological Studysupporting
confidence: 91%
“…Previous studies demonstrated that impaired or delayed healing was serious problem in some metabolic diseases including DM [6,8,9,10,11], because of several factors such as differentiation of the extracellular matrix dysfunction in fibroblasts and epidermal cells, and poor angiogenesis, e.g. [6,11].…”
Section: Histopathological Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect IF was performed as previously described [28]. Brie y, the tumor slides were incubated with the appropriate antibody (CD3, CD4 and CD8) at 4˚C overnight in a wet box.…”
Section: If Detectionmentioning
confidence: 99%
“…Ji et al [56] investigated the expression level of receptors for advanced glycation end products during the healing of diabetic wounds in mice. Their results showed that the process of repairing diabetic wounds differs from that of normal wounds, suggesting that the parameters used to assess the age of the normal wound may not be applicable to the diabetic wound.…”
Section: Biomarkers Of Wound Agingmentioning
confidence: 99%